Hubungan Kebahagiaan Otentik dan Belas Kasih Diri Pada Siswa SMA Keturunan Banjar - Sanjaya, Sanjaya; Haryadi, Rudi; Aminah, Aminah (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The aim of this research is to determine the positive and significant correlation between authentic happiness and self-compassion in high school students of Banjar descent in Banjarmasin City. This research is quantitative research with a correlational design. Authentic happiness and self-compassion in 387 high school students of Banjar descent in Banjarmasin City were measured using the authentic happiness scale (α = 0.654) and self-compassion scale (α = 0.614) which was developed in Indonesia. The Pearson Product Moment correlation test is used to analyze data and prove the hypothesis that is built. The research results show that there is no positive and significant relationship between authentic happiness and self-compassion among students of Banjar descent in Banjarmasin City (Sig. = 0.148 < 0.05; r = -0.074; n = 387). Based on the research results and methods used in this research, it is recommended that future researchers further explore the meaning of happiness and self-compassion in Banjar students, as well as develop a measuring tool for happiness and self-compassion that is more adaptive to Banjar culture.